Metode Memahami Islam Rahmatan Lil ‘Alamin - Yudi Kuswandi (STAI Siliwangi Bandung, 2022)
There are various methods and approaches to understanding religion in producing knowledge of its teachings (knowing), with various riyadhah (practices) that produce skills in performing rituals (doing), and finally realizing the teachings of religious doctrines in daily behavior (being). Unfortunately, in understanding religion, there are still many who use partial methods and approaches; as a result, we can still encounter disputes and contradictions in society. So, by understanding the method used, it is hoped that a sense of tasamuh will arise among the people. Because the experience of religious rites is subjective, involves personal emotions, and is influenced by the goals and backgrounds. Because the methodology for understanding Islamic teachings can be quantitative and qualitative, the truth can differ depending on the approach used. So, we must respect these two truths, through husnudhan (kindness), tasamuh (tolerance), and salāmatu al-shudūr (open-mindedness), accepting the necessity of differences.